2005
DOI: 10.1007/s00134-005-2564-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of immunonutrition in a heterogeneous intensive care population

Abstract: The results of this largest randomized, controlled trial found that in the general ICU population immunonutrition has no beneficial effect on clinical outcome parameters. These results are consistent with the literature that is currently available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 48 publications
0
72
0
4
Order By: Relevance
“…The only study in septic patients showed improved survival, but had limitations in study design [623]. Other studies suggested no benefit or possible harm in the subgroup of septic patients [621,624,625]. Some authors found improvement in secondary outcomes in septic patients, such as reduced infectious complications) and hospital LOS, but the relevance of these findings in the face of potential harm is unclear.…”
mentioning
confidence: 99%
“…The only study in septic patients showed improved survival, but had limitations in study design [623]. Other studies suggested no benefit or possible harm in the subgroup of septic patients [621,624,625]. Some authors found improvement in secondary outcomes in septic patients, such as reduced infectious complications) and hospital LOS, but the relevance of these findings in the face of potential harm is unclear.…”
mentioning
confidence: 99%
“…PEG is relatively safe and it is minimally invasive when compared with open surgical procedures. The indications and contraindications for PEG placement have been reported and are established [ 23 ]. The technique, however, has been standardized and does need further elaborations except to note that there are two ways of advancing the wire: the push and the pull technique.…”
Section: Percutaneous Endoscopic Gastrostomy (Peg)mentioning
confidence: 98%
“…Galban et al [ 22 ] studied 176 septicemia patients and reported that the group that received a nutritional supplement with enhanced arginine had a signifi cantly reduced death rate compared to the control nutritional supplement group (19 % vs. 32 %). Kieft et al [ 23 ] studied 597 ICU patients and compared a group that received a nutritional supplement containing enhanced arginine to a control group. They found that there were no differences between the groups in death rate, infection rate, or the number of days in the ICU.…”
Section: Trends Of Clinical Studies Related To Argininementioning
confidence: 99%
“…2 The use of immune-enhancing enteral formulas, supplemented with glutamine, arginine, nucleotides, or an increased -3:-6 fatty acid ratio, has been studied in critically ill patients. Results of these studies ranged from reduced requirements for mechanical ventilation, 99 to no effect, 100 to increased mortality in patients with sepsis. 101 Some studies have confirmed benefits of eicosapentaenoic acid (EPA), ␥-linolenic acid (GLA), and antioxidants in patients with acute respiratory distress syndrome (ARDS) or acute lung injury (ALI).…”
Section: Our Approach To Nutrition Support In CCImentioning
confidence: 99%